Ethnobotany and Phytochemistry of the genus Eremostachys Bunge - Mohammadhosseini, Majid; Frezza, Claudio; Venditti, Alessandro; Akbarzadeh, Abolfazl (Current Organic Chemistry, 2019)
In this review, the species from the genus Eremostachys Bunge are described and explored from different standpoints. In particular, the main attention is focused on phytochemistry also with reference to the biogenesis of the most important class of chemotaxonomic marker, the iridoids, and their co-occurrence with volatile terpene components of essential oils which own the same biogenetic precursors. The ethnopharmacological implications of the plants belonging to this genus are also reported in detail. Nevertheless, a few morphological and botanical details of Eremostachys are also presented, as well as some topics about its chemotaxonomy and pure pharmacology. Based on the data reported in the literature, different species of the genus Eremostachys show important and interesting peculiarities under all these aspects that are extensively discussed and commented.
Keywords: iridoids